DNA and RNA editing of retrotransposons accelerate mammalian genome evolution. (26th February 2015) - Knisbacher, Binyamin A.; Levanon, Erez Y.
Abstract : Genome evolution is commonly viewed as a gradual process that is driven by random mutations that accumulate over time. However, DNA‐ and RNA‐editing enzymes have been identified that can accelerate evolution by actively modifying the genomically encoded information. The apolipoprotein B mRNA editing enzymes, catalytic polypeptide‐like (APOBECs) are potent restriction factors that can inhibit retroelements by cytosine‐to‐uridine editing of retroelement DNA after reverse transcription. In some cases, a retroelement may successfully integrate into the genome despite being hypermutated. Such events introduce unique sequences into the genome and are thus a source of genomic innovation. adenosine deaminases that act on RNA (ADARs) catalyze adenosine‐to‐inosine editing in double‐stranded RNA, commonly formed by oppositely oriented retroelements. The RNA editing confers plasticity to the transcriptome by generating many transcript variants from a single genomic locus. If the editing produces a beneficial variant, the genome may maintain the locus that produces the RNA‐edited transcript for its novel function. Here, we discuss how these two powerful editing mechanisms, which both target inserted retroelements, facilitate expedited genome evolution.